An overview of company valuation techniques with implementation to major Turkish companies - Akbulut, Saltuk Buğra. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2006., 2006)
The objectives of this thesis are to review the theoretical literature on company valuation, to define a valuation procedure based on findings and to implement such procedure on four major Turkish companies from different industries. Under the scope of thesis, an extensive literature survey on the company valuation is undertaken. The literature survey covers a review of the main company valuation techniques, their fundamental assumptions, application areas and limitations, alternative methods and an overall comparison. The survey focuses on discounted cashflow valuation and relative valuation while a general introduction to contingent claim valuation is made. Then, a valuation procedure based on discounted cashflow valuation and relative valuation techniques is developed by using the findings of the literature survey. The procedure is composed of successive steps expressed in mathematical form where appropriate. Finally, the valuation procedure is implemented on four major Turkish companies from different industries. By implementing the procedure, a valuation range for each company is calculated. Then, the results obtained with the valuation procedure are compared with the observed market values of these companies on Istanbul Stock Exchange between 25 May 2005 and 25 May 2006. The results show that the valuation procedure can be used to identify the long-term value range of the companies covered in this study.
Keywords: Corporations -- Valuation.